Experience in the Treatment of Wounds of Circulatory Organs in the Chest and Main Vessels of Other Localizations in Wartime - Nazar Z. Hrabovskyy (Ukrainian Journal of Cardiovascular Surgery, 2022)
The article presents the principles of providing care for injuries to the heart, aorta, pulmonary artery, or other main vessels. The described principles can be applied in the treatment of civil injuries.The aim. Consider a treatment tactic in the cases of heart and main vessels combat injuries using own experience.Materials and methods. Twelve cases of combat wounds of blood circulation organs in the chest were analyzed: 5 gunshot injuries of the subclavian vessels, 4 gunshot injuries of the heart, 1 gunshot injury of the ascending aorta, 1 gunshot injury of the pulmonary artery and 1 suspected gunshot injury of the left ventricle.Also we analyzed 78 cases of combat gunshot injuries of main vessels of other locations: 3 injuries of vessels of the neck, 68 injuries of main vessels of limbs, 6 injuries of iliac arteries, 1 injury of abdominal aorta.Most of the operations, with the exception of those that required artificial blood circulation, were performed in advanced hospitals at the II level of military medical evacuation, which enabled to shorten the time from injury to the performance of the final surgical intervention and save life or limbs.Results and discussion. Two cases with penetrating wounds to the chest and damage to the subclavian vessels were fatal. Death was attributed to uncontrolled chest bleeding.Among the 78 cases of injury of main vessels of other locations, one case with damage to the iliac arteries was fatal, and death also occurred as a result of uncontrolled massive intra-abdominal bleeding.Conclusions. Wounded individuals with unstable hemodynamics against the background of ongoing massive bleeding and with suspicion of injury of the heart or main vessels in the chest should be operated on immediately. Due to the urgency of performing such operations and impossibility of an adequate additional examination, localization and degree of the damage to the organs of the circulatory system is determined during the operation. A thoracoscopic approach can be used in stable patients with non-penetrating gunshot wounds to the heart.In the relatively stable condition of patients with an established injury of the heart, aorta, or pulmonary artery, it is advisable to perform additional examinations. Patients with trauma to the main vessels of the extremities and ischemia thereof need rapid revascularization.